The impact of climate risk on low-carbon innovation: evidence from listed companies in China - He, Siyuan (Frontiers in Climate, 2025)
Given the pivotal role of climate risk in fostering sustainable corporate growth, this factor warrants further investigation in the context of low-carbon innovation. Drawing on firm-level data from Chinese enterprises during the 2007–2022 period, our research establishes climate risk as a significant driver of corporate low-carbon innovation, with transition risk proving more influential than physical risk. The analysis of underlying mechanisms reveals that climate risk stimulates low-carbon technological innovation primarily through two channels: increased research and development expenditures and enhanced environmental certification efforts. Examination of heterogeneous effects demonstrates that climate risk’s innovation-enhancing potential is particularly pronounced among three distinct groups: enterprises not designated as key pollution monitoring units, firms operating in less polluting industries, and businesses located in China’s eastern regions. These insights provide valuable implications for policymakers and businesses on leveraging climate risk to drive low-carbon innovation while achieving balanced sustainable development in terms of Research and Development investment and pollution control dimensions.